Experimental and Numerical Study on the Composite Column Behavior: Loess Soil Reinforced by Concrete-Stone Column - Mahmood A. Salam; Qiyao Wang; Jinbo Huang (Salehan Institute of Higher Education, 2022)
Stone columns are an effective approach to improving the bearing capacity of weak soils, which has led to increased interest in the improved soil method being further developed and expanded. In addition, enhancing the bearing capacity of stone columns has recently received great attention. This paper studies the effects of embedded concrete parts on the stone columns' bearing capacity and bulging failure. Moreover, arranging solutions to the problem of bulging failure and reduced bearing capacity of stone columns and understanding the stone columns' failure after reinforcement by comparing the results. Stone columns are either embedded in a solid concrete part or unreinforced were examined using large-scale laboratory experiments, and numerical simulation was performed using ABAQUS. The models test with a scale factor of 1:7 was employed. The results demonstrated that using a concrete part on the top of the stone column greatly increases its bearing capacity and the efficiency of the surrounding soil. Concrete-stone columns (CSCs) show stress concentration ratio (n) enhancement and significant resistance to bulging failure deformation. The concrete-stone column shows an enhancement related to increasing the concrete part length; also, the CSCs stiffness increases the surrounding loess soil capacity. The horizontal stresses of CSCs demonstrate the type of column failure behavior; the column may fail due to shear stress in a long concrete part case. Doi: 10.28991/CEJ-2022-08-10-01 Full Text: PDF